Efficiencies of the drift chambers in the EMMA experiment - Monto, Tiia (2013)
Cosmic rays are high-energy subatomic particles which travel almost at the speed of light all over the space. The shape of the cosmic ray energy spectrum is measured experimentally, but it is not perfectly understood. The slope of the spectrum at high energies is constant up to the knee energy (about 10^15 eV) where the slope steepens. The knee has been tried to be explained by several models which aim to describe the origin and the acceleration mechanisms of the cosmic ray. The stars and the shockwaves from supernova explosions are believed to be at least a part of cosmic ray evolution.